Variability in the golf swing and its effect on performance accuracy - Fitzpatrick, K. D. J.; Anderson, R. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Preliminary results suggest that certain kinematic variability effects the accuracy of a golf shot. A trade off between accuracy and distance hit may cause this variability. The KV of certain joints is of more influence over PV than others and furthermore the specific joint with greatest influence over the PV can fluctuate between golfers. Additional analysis is required to establish if this variability is significant with respect to the accuracy of the golf shot.